Non-linear integer programming by Darwin and Boltzmann mixed strategy - Tian, Peng; Ma, Jian; Zhang, Dong-Mo (European journal of operational research, 1998)
Non-linear integer programming is an NP-complete problem with extensive theoretical and practical backgrounds. Based on the proposed Darwin and Boltzmann mixed strategy, a general stochastic iterative algorithm for the NIP problems is presented. The algorithm synthesizes the advantages of the Darwin strategy and the Boltzmann annealing strategy. It converges asymptotically to the global optimums and has shown to be polynomial in complexity. The experimental evaluations also show that the proposed algorithm is more efficient than the simulated annealing algorithm.